When Prospective Mathematics Teacher Students Face Inclusive Classes - Mumtaz, Nafis; Jauhar Riyadi , Jauhar Riyadi; Sumbaji Putranto, Sumbaji Putranto (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
Learning mathematics in inclusive classes has its own challenges. This is due to the heterogeneity of student characteristics in the class. Therefore, special knowledge is needed that prospective teacher students must have to deal with inclusion classes, so this research aims to analyze students' readiness to teach in inclusion classes. Qualitative descriptive research was used to describe the results of interviews regarding the readiness of 16 mathematics education students at one of the state Islamic universities in Indonesia. The results of the research show that students in semesters 5 and 7 have good understanding and show readiness to teach in inclusive classes, while students in semesters 1 and 3 also have good readiness to teach in inclusive classes, but they still need prior training in inclusive education courses before being placed in inclusion classes because understanding about children with special needs is still limited. This research has an impact on increasing the skills and empathy of prospective teachers, access and achievement of students with special needs, the quality and readiness of educational institutions, inclusive education policies, as well as public awareness of the importance of inclusion and social acceptance.